Systematiskt brandskyddsarbete vid Fasadelement Verkstads AB - Bengtsson, Per; Håkansson, Tor (2011)
AbstractOn the 1st of January 2004 the Civil Protection Act took effect and thus replaced the Rescue Services Act. One of the goals of the new legislation was to further distinguish the different areas of responsibility regarding fire safety. In order to clarify some parts of the new law, the Swedish Rescue Services Agency issued a general recommendation (SRVFS 2004:3) which amongst other things states that the estate agent or the usufructuary are responsible for carrying out and documenting a fire safety management system to uphold a reasonable level of fire safety.The theoretical aim of this paper was to define what should be included in such a fire safety management system and to try to give an understanding of other factors that may have an impact on risk management as a whole. The theory has then been put to practical use when designing the fire safety management system for Fasadelement Verkstads AB, a small company in the Luleå area that specializes in manufacturing steel products for the building- and transport industry.By studying the general recommendation (SRVFS 2004:3) along with literature and guidelines of some Swedish municipalities it was concluded that a fire safety management system should include the following:• Policy• Organization & Areas of responsibility• Description ofo Building characteristicso Activitieso Fire safety installations• Risk assessment & Risk reduction plan• Training, information and fire safety drills• Fire safety regulations• Control and maintenance routines• Follow-up routinesThe mere existence of a documented fire safety management system is not enough to achieve a satisfactory standard regarding fire safety. There needs to be an understanding throughout the entire organization in order for such a system to work. The management must show commitment and willingness to allocate recourses and the workforce must have an understanding and respect regarding fire safety issues. In order to achieve this a positive safety culture is needed.A well working fire safety ...